Start of a life health risk, struggles and coping as experienced teenage mothers - Marris R. Reyes; Benilda M. Hangdaan; Kristine Mae C. Sadang; Marilyn G. Pasion (International Journal of Public Health Science (IJPHS), 2021)
Motherhood plays a vital role in society. It greatly influences the personality and disposition of a child. Teenage pregnancy is one of the major international social issues; nonetheless, the available literature seemed to address this issue quite indecorously. Thus, this study intended to identify the dynamics and causes of teenage pregnancy based on the context of those who experienced it. This study mainly focused on the personal health risk experiences, struggles, and coping of teenage pregnancy. A semi-structured in-depth interview with 35 teenage mothers was conducted. The researchers carefully transcribed the conversations, then read and re-read, then summarized the musings and verbalizations of the participants. A descriptive Phenomenological approach was utilized to analyze the data. Then, the missing psyche, unwanted, social judgment, embrace (MUSE) Phase of Teenage Pregnancy emerged. This was validated using “critical-friend and correspondence technique”. Each phase reflects the onset, coping and struggles on becoming a teenage mother from conception to rearing the child. The discussion poses a unique perspective on understanding the phases of teenage pregnancy coming from the point of view of those who experienced it, which is vital in making efforts to prevention and intervention.